Local Suppression of T Cell Responses by Arginase-Induced L-Arginine Depletion in Nonhealing Leishmaniasis - Modolell, Manuel; Choi, Beak-San; Ryan, Robert O.; Hancock, Maggie; Titus, Richard G.; Abebe, Tamrat; Hailu, Asrat; Müller, Ingrid; Rogers, Matthew E.; Bangham, Charles R. M.; Munder, Markus; Kropf, Pascale (PLOS Neglected Tropical Diseases, 2009)
Author Summary Leishmania parasites are obligate intracellular pathogens that predominantly invade macrophages. Instruction of macrophages by T cell-derived signals is required to control parasite growth. Here we show that arginase, an enzyme induced in Leishmania-infected macrophages, is highly expressed at the site of pathology in nonhealing lesions and causes local depletion of L-arginine, an amino acid that is essential for efficient T cell responses. This local reduction in L-arginine impairs the capacity of T cells in the lesion to proliferate and to produce interferon-γ, one of the signals required for parasite killing. Cure of Leishmania infection by drug treatment is accompanied by a reduction in arginase activity and restoration of T cell effector functions. Furthermore, inhibition of arginase, as well as injection of L-arginine, reverses immunosuppression and results in more efficient control of parasite replication. Our results identify a novel mechanism accounting for ineffective T cell responses in nonhealing leishmaniasis.